2013
DOI: 10.3171/2012.9.jns12702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and functional recovery of traumatic isolated oculomotor nerve palsy in mild head injury with sphenoid fracture

Abstract: Limited eye movement may be a major factor that negatively affects functional recovery after mild head injury. Sphenoid fracture might be one of the potential mechanisms involved in traumatic isolated oculomotor nerve palsy after mild head injury. Surgical decompression should be considered when there is evidence of bone compression of the superior orbital fissure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Interestingly, we found that injuries to the oculomotorius, trochlear and abducens nerve after head trauma has been described by authors in the ophthalmology and neurosurgery fields [82][83][84][85][86][87]. The trochlear and abducens nerve are most vulnerable among the intraorbital nerves due to their structure, length and intracranial route [82] and these nerves can be injured even after minor head trauma [82,85]. These findings motivate meticulous examinations of eye movements in trauma patients and wide indications for referral to an ophthalmologist, especially in patients having diplopia in the primary position of gaze [4].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Interestingly, we found that injuries to the oculomotorius, trochlear and abducens nerve after head trauma has been described by authors in the ophthalmology and neurosurgery fields [82][83][84][85][86][87]. The trochlear and abducens nerve are most vulnerable among the intraorbital nerves due to their structure, length and intracranial route [82] and these nerves can be injured even after minor head trauma [82,85]. These findings motivate meticulous examinations of eye movements in trauma patients and wide indications for referral to an ophthalmologist, especially in patients having diplopia in the primary position of gaze [4].…”
Section: Discussionmentioning
confidence: 58%
“…This was surprising since diplopia usually is due to hinged eye muscles, fibrosis or malposition of the eye (dystopia and/or enophthalmos) according to the literature [6,15]. Interestingly, we found that injuries to the oculomotorius, trochlear and abducens nerve after head trauma has been described by authors in the ophthalmology and neurosurgery fields [82][83][84][85][86][87]. The trochlear and abducens nerve are most vulnerable among the intraorbital nerves due to their structure, length and intracranial route [82] and these nerves can be injured even after minor head trauma [82,85].…”
Section: Discussionmentioning
confidence: 82%
“…1e3 Previous studies have revealed that the recovery rate of ptosis was rapid and high (95%e100%), while it was lesser for external ophthalmoplegia, and least for internal ophthalmoplegia. 7,8 However isolated ONP after mild head injury being rare, its clinical and functional outcome has not been evaluated in detail. It has also been suggested that these patients in whom no lesion is demonstrated on the initial CT scan have a good prognosis, with a greater chance of recovery 9 as was observed in this case, who showed a nearly complete recovery within such a short period.…”
Section: Resultsmentioning
confidence: 99%
“…4 Of the 20 patients with ptosis, 19 of 20 (95%) recovered, and 15 of 18 (83.3%) with external ophthalmoplegia recovered. Trauma in the region of the superior orbital fissure can damage the trunk or divisions of the oculomotor nerve.…”
Section: Discussionmentioning
confidence: 93%